Development of Local Wisdom-Based Learning Media with Prezi Applications in Social Arithmetic - Choirudin Choirudin (Jurnal Teknologi Pembelajaran, 2021)
The aim study to create and develop local wisdom-based learning media with Prezi applications in Social Arithmetic Materials. This type of research is Research and Development (RND), using development steps according to Borg & Gall which has been transformed by Sugiyono. The development steps are limited to six steps. Among them; 1) Results of Need Analysis; 2) Problem Identification and Data Collection; 3) Product Design Results; 4) Design Product Validation; 5) Design Revision Results (Initial Product); 6) Small Group Trial; and 7) Field Trials (Large Group Trial). Local wisdom-based learning media have been developed with the application of Prezi on social arithmetic material by collecting data on local wisdom on the livelihood of Buminabung residents by taking documentation in the form of photos and information related to the local wisdom put them on the slide Prezi. The development of local wisdom-based learning media with the application of Prezi on social arithmetic material is feasible to use in learning. The assessment of material experts and media experts with an assessment of 80% in the feasible category and 91% in the very feasible category. The results of the trials carried out were small group trials in class VII A with a feasibility percentage of 76% in the feasible category. In the field trials conducted by class VII A MTs Ma’arif 05 Buminabung, the percentage was 79% in the feasible category.